Study of potent CDK7 inhibitor secondary metabolites from Tecomella undulata. Issue 22 (17th November 2022) - Khandelwal, Poonam; Tiwari, Harshita; Sharma, Venu; Mali, Deepak; Vyas, Pooja; Wadhwani, Barkha Darra
Abstract: Chemical investigation of the petroleum ether extract of heartwood of Tecomella undulata led to the isolation of tectonaquinone B (1), 2-methylquinizarin (2) along with tecomaquinone I (3), lapachol (4), 2-isopropenylnaphtho[2, 3-b]-furan-4, 9-quinone (5), dehydro-α-lapachone (6), α-lapachone (7), and β-lapachone (8). This is the first report of isolation of tectonaquinone B and 2-methylquinizarin from this plant. The structures of compounds were elucidated by advanced spectroscopic methods. Molecular docking study for potential inhibitory action toward CDK7 (cyclin-dependent kinase 7) were performed, which proved that these compounds have high binding affinities with the receptor protein (CDK7). 2-Methylquinizarin exhibited best docking score (−7.70 kcal/mol) among all the tested compounds. The present study showed that 2-methylquinizarin may exhibit potent anticancer activity through inhibiting CDK7 via interaction with Met94. Graphical Abstract: UF0001